Effect of IT investment announcement on company value: evidence from Indonesia stock exchange - Siska Aprilia Oktaviani; Muhammad Miqdad; Wahyu Agus Winarno (Penerbit Universiti Kebangsaan Malaysia, 2023)
This study examines the effect of IT investment on company value in the Indonesian Stock Exchange. The method used is the event study analysis. The beta used to calculate abnormal returns are the traditional beta and the corrected beta of Dimson and Scholes-Williams given that the Indonesian market is a thin trading market. The results of this study indicate that there is an effect of IT investment announcements on firm value on the post-event window. The results also show that investors tend to react positively to IT investment announcements made by companies in 2020 thus suggesting that the occurrence of the COVID-19 pandemic has effectively affected investors in processing new information regarding technology investments made by companies. The study is expected to provide benefits to assist policy making on Indonesia Stock Exchange and Capital Market and Financial Institutions Supervisory Agency (Bapepam-LK) regarding the disclosure of company information on the implementation of IT investments.